The Effect of Transformational Leadership and School Climate on Job Satisfaction of Non-ASN Teachers at Public Elementary Schools in the Education Office Sub-Department I of West Jakarta Administrative City - Rafi Taris Mafazi (Eduvest - Journal of Universal Studies, 2026)
The background of this study is to examine how transformational leadership and school climate influence teacher job satisfaction. This study aims to analyze the influence of transformational leadership and school climate variables on job satisfaction and analyze the influence of transformational leadership on school climate. The method in this study is a quantitative research type with an explanatory approach with data sources used in the form of numbers from survey results given to a number of samples. The results of this study are that there is a positive and significant influence between transformational leadership on job satisfaction, then there is a positive and significant influence between school climate on teacher job satisfaction, meaning that a mutually supportive school environment, and a principal who provides motivation can increase teacher job satisfaction. The results of descriptive analysis with a normality test on the transformational leadership variables of school principals using the one sample Kolmogorov Smirnov test, were obtained by Asymp.